Synergistic Cytotoxicity of Natural Gallic Acid from Vitis vinifera and Tamoxifen in Human Osteosarcoma U2OS - Hapidin, Hermizi; Sidek, Nur Najihah; Shamsuddin, Shaharum (Malaysian Applied Biology, 2026)
Osteosarcoma is a prevalent and aggressive bone malignancy, primarily affecting children and adolescents. While tamoxifen (TAM) is a commonly used chemotherapeutic agent, its application is often limited by adverse side effects. Gallic acid (GA), a naturally occurring polyphenol, has demonstrated promising anticancer properties and may offer a safer alternative or adjunct in cancer therapy. This study investigates the effects of GA alone and in combination with TAM on the viability and morphology of human osteosarcoma (U2OS) cells. An in vitro model was employed using the MTT assay to assess cell viability after 72 hr of treatment. The half maximal inhibitory concentration (IC50) and combination index (CI) were calculated to evaluate cytotoxicity and drug interaction. Three combination ratios of GA:TAM (75:25, 50:50 & 25:75) were tested. GA and TAM alone exhibited IC50 values of 8.258 ± 1.047 µg/mL and 1.814 ± 1.205 µg/mL, respectively. The 25:75 combination yielded the lowest IC50 (1.475 ± 1.189 µg/mL) and a CI of 0.637, indicating a synergistic effect. Other combinations showed higher IC50 and CI values, suggesting reduced efficacy. Morphological analysis using phase contrast microscopy revealed apoptotic features such as cell shrinkage and rounding in treated cells, particularly in the 25:75 combination group. In conclusion, GA, especially when combined with TAM at a 25:75 ratio, enhances therapeutic efficacy while potentially reducing toxicity. This combination may represent a promising strategy for improving osteosarcoma treatment outcomes.